Preparation and Performance Study of MXene-Regulated Ethylene Glycol-Induced WO3 Film - Yuqi Wang; Yong Liu; Minmin Wang; Wenjun Wu; Maofei Tian; Tao Zhu (Micromachines)
This study introduces the development of a W-M1.0 electrochromic film, characterized by a “coral”-like TiO2@WO3 heterostructure, synthesized via a hydrothermal process leveraging the inherent instability of MXene. The film showcases exceptional electrochromic performance, with a coloring response time of 2.8 s, a bleaching response time of 4.6 s, and a high coloring efficiency of 137.02 cm2C−1. It also demonstrates a superior light modulation ability of 73.83% at 1033 nm. Notably, the W-M1.0 film exhibits remarkable cyclic stability, retaining over 90% of its initial light modulation capacity after 4000 cycles, outperforming many existing electrochromic materials. The film’s enhanced performance is credited to its coral-like structure, which boosts the specific surface area and promotes ion transport, and the TiO2@WO3 heterojunctions, which enhance charge transfer and stabilize the material. Devices fabricated with the W-M1.0 film as the cathode and a PB film as the anode exhibit a seamless transition from dark blue to colorless, underscoring their potential for smart window and dynamic glass applications.